The far right, the Euromaidan, and the Maidan massacre in Ukraine. (15th December 2019) - Katchanovski, Ivan
Abstract: This study examines the role of the far right in the Euromaidan in Ukraine, primarily in the Maidan massacre and other key cases of violence. The involvement of far‐right organizations in these crucial events in the Ukrainian and world politics has been politicized and polarized in Ukraine, the West, and Russia. This study analyzes various data sources, such as online live streams and TV broadcasts, videos, broadcasts of the Maidan massacre trials, the database of court decisions in Ukraine, media reports, and field research on the Maidan. The findings reveal that radical nationalist and neo‐Nazi organizations had significant but minority representation among the Maidan leadership and protesters. However, the analysis shows that the far‐right organizations and football ultras played a key role in political violence such as attempting to seize the presidential administration and the parliament. It reveals involvement of the Right Sector in violent clashes with the Berkut special police force during the highly publicized dispersal of Maidan protesters on November 30, 2013. The Right Sector and Svoboda had crucial roles in the violent overthrow of the Yanukovych government, in particular, in the Maidan massacre of the protesters and the police.